Efficiency of biochar and compost on soil bio-chemical properties and yield of knol-khol (Brassica oleracea L.) - Peeyush, Sharma; Vikas , Abrol; Satesh, Kumar; Reetika , Sharma; Maanik; Haziq , Shabir; Stanzin, Khenrab (Plant Science Today, 2025)
A field experiment was conducted to assess how the combined application of biochar with various organic amendments affects the soil biochemical properties and the yield characteristics of knol-khol (Brassica oleracea var. gongyloides L.). The outcomes showed that biochar with organic amendments substantially enhanced the biological characteristics of the soil as compared to the control treatment. There was a notable increment in soil microbial biomass carbon by 33.27 % and dehydrogenase activity by 5.68 % following the integrated application of farmyard manure, vermicompost and biochar (T8). In addition, several knol-khol growth metrics showed significant improvement in T8 compared to the control, including leaf number (1.36 times), plant height (1.38 times) and knob diameter (2.3 times). In T8, the knolkhol production increased by a remarkable 3 times, demonstrating the beneficial effects of the combined treatment on marketable output. The results of the experiment showed that T8 had significantly higher levels of accessible nitrogen (12.38 %), available potassium (8.54 %), available phosphorus (24.19 %) and organic carbon (9.5 %) than the control. According to this, the concurrent application of farmyard manure, vermicompost and biochar enhanced soil fertility and boosted plant and microbial nutrient availability, which in turn led to higher profitability.